Integrating experiential learning and soft skills through community services towards 21st-century education: Satisfaction index analysis - Normah Abdul Latip; Jabil Mapjabil; Christina Andin; Jeannet Stephen; Nor-Ina Kanyo; Mohamad Pirdaus Yusoh; Ayesah Uy Abubakar (International Journal of Special Education (IJSE), 2022)
2lst-century education in the future is an important theme debated today. Discussions focus on the most relevant knowledge and skills to prepare our children for the rapidly changing society. Many of these skills are categorized as "2lst-century skills" that incorporate soft skills through the concept of experiential learning. Soft skill development is crucial for student empowen11ent, and the role of the high institution become more challenging with the skill not being fon11ally taught in the education system. The Study purposely determined the level of satisfaction regarding soft skills in students among the local participant towards the community. The random sampling method uses to choose the respondent from three community projects. The questionnaire establishes as an instrument to collect required information after the project ends, and ninety respondents from three community projects fillup the form accordingly. Analysis on (7) seven soft skills with Likert scale approach indicates interpersonal skill is the most highlighted by a community project participant. The preliminary finding indicates that most respondents were very satisfied with the community project. Fmihern1ore, they emphasize that the students demonstrated soft skills during the project activity.